Spontaneous Subarachnoid Hemorrhage Caused By Aneurysm: The Retrospective Analysis of 328 Cases - İlhan, Yılmaz; Eseoğlu, Metehan; Demirgil, Bülent Timur (Fırat University, 2012)
Objective: In this study the factors that affect the prognosis in aneurysm based spontaneous surbarachnoid hemorrhage are reviewed accompanied by the literature. Materials and Methods: 328 SAH cases who were referred to our hospital between January 1995-2005, were analyzed retrospectively in terms of aetiological, clinical and radiological findings. Female/Male rate was found as 1,2. Ages of the patients were changing from 4 to 93. Neurological evaluations of the patients were made according to the Glasgow Coma Scale and Yasargil criteria; and CT findings were evaluated according to the Fisher classification. Besides we analyzed the relation between age, gender and season. The results were discussed by taking the literature into account. Results: The most frequent reason of spontaneous surbarachnoid hemorrhage caused by aneurysm is the anterior communicane artery aneurysm. The average age was determined as 48.6. The most common complaint of the patients when they were referred to our clinic was headache (70.1%). SAH diagnosis was done via cranial CT for 305(93%) cases of all 328 cases. The frequency of observation of SAH seemed to be on increase especially in autumn. According to the Yasargil classification; the most common phase that observed in the cases was ‘ Phase 2a' , and according to Fisher classification the most common phase was ‘Phase 2'. Conclusion: CT is the most common method to diagnose SAH in the first 72 hours. Magnetic Resonance or Lomber Puncture should be applied when diagnose is not possible with CT. Digital substraction angiography is the first.

Amaç: Bu çalışmada anevrizma kökenli spontan subaraknoid kanamalarda prognozu etkileyen faktörler literatür eşliğinde gözden geçirildi. Gereç ve Yöntem: Bu çalışmada Ocak 1995-2005 yılları arasında kliniğimize başvuran 328 SAK olgusu retrospektif olarak, etyolojik klinik ve radyolojik bulgulara göre incelendi. K/E oranı 1,2 olarak bulundu. Yaş dağılımı 4 ile 93 yaş arasındaydı. Hastaların nörolojik değerlendirilmesi Glaskov Koma Skalası ve Yaşargil kriterlerine göre, Bilgisayarlı Tomografi bulguları (BT) ise; Fisher sınıflandırılmasına göre değerlendirildi. Ayrıca çalışmamızda Sak'ın yaş, cinsiyet ve mevsimsel ilişkisi incelendi. Sonuçlar literatürde karşılaştırılarak tartışıldı. Bulgular: Anevrizmaya bağlı spontan subaraknoid kanamaların ensık sebebi (%32,8) anterior komminikan arter anevrizmasıdır. Ortalama yaş 48,6 olarak bulundu. Başvuru anındaki ensık şikayetin başağrısı (%70,1) olduğu görüldü. 328 olgunun 305'inde (% 93) subaraknoid kanamaların tanısı kranial BT ile kondu, subaraknoid kanamaların görülme sıklığının özellikle sonbaharda arttığı tespit edildi. Yaşargil sınıflmasına göre vakalarda ensık Evre 2a, Fisher sınıflamasına göre ensık Evre 2 tespit edildi. Sonuç: SAK ta ilk 72 saatte tanı koymada BT en yaygın yöntemidir. BT ile tanı konulamayan durumlarda Magnetik Rezonans veya Lomber Ponksiyon yapılmalıdır. Dijital substraksiyon anjiyografi anevrizma tespitinde ilk tercihtir.
Anevrizmaya Bağlı Spontan Subaraknoid Kanamalar: 328 Vakalık Retrospektif İnceleme